FACTORS AFFECTING PERFORMANCE OF COURSE CENTER MANAGEMENT IN URBAN AREAS - Anwar Sanusi; Victor Wiley; Thomas Lucas (Sanata Dharma University Yogyakarta, 2020)
Observing the role of course center to provide public access to informal learning is rare in many literature body. In addition, there is lack of information about strategies implemented by course center to improve their performance in managing the course center management. The paper analyzes the factors influencing the performance of course center in Jakarta region to fulfill the learner needs. A novelty is proposed in this paper as a model to understand how the course center can improve their performance to provide informal learning and the performance of center management. The paper uses a quantitative type with purposive sampling questionaire which distributed to the tutor, course center manager, course owners and office staffs. Our analysis result showed that the course center needs integrating their strategies to maximize their function in the community. This research is useful to provide input to the government and course managers so that the course center in Jakarta can improve their performance to fulfill the learner needs.DOI: 10.24071/ijiet.2020.040112